2016
DOI: 10.1007/s13361-016-1364-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential Mobility Spectrometry-Hydrogen Deuterium Exchange (DMS-HDX) as a Probe of Protein Conformation in Solution

Abstract: Abstract. Differential mobility spectrometry (DMS) is an ion mobility technique that has been adopted chiefly as a pre-filter for small-to medium-sized analytes (<1 000 Da). With the exception of a handful of studies that employ an analogue of DMS-field asymmetric waveform ion mobility spectroscopy (FAIMS)-the application of DMS to intact biomacromolecules remains largely unexplored. In this work, we employ DMS combined with gas-phase hydrogen deuterium exchange (DMS-HDX) to probe the gas-phase conformations g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
(57 reference statements)
0
20
0
Order By: Relevance
“…In an ideal case, the DMS coupled to HDX would allow for determining the liquid-phase structure of a particular protein and evaluating global structure of protein in solution. DMS-HDX was used to determine charge distribution (800–2400 m/z) and compensation voltages of nTau and pTau (Zhu et al 2016). While it was found that nTau existed in an unfolded state, pTau existed in a mix of states.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…In an ideal case, the DMS coupled to HDX would allow for determining the liquid-phase structure of a particular protein and evaluating global structure of protein in solution. DMS-HDX was used to determine charge distribution (800–2400 m/z) and compensation voltages of nTau and pTau (Zhu et al 2016). While it was found that nTau existed in an unfolded state, pTau existed in a mix of states.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…The level of incorporation of deuterons from the surrounding gas by a protein depends on the surface accessibility of its protons and thus on its conformation. Even though low levels of exchange have been correlated with compact structures and higher levels of exchange with more elongated conformations, the actual mechanisms of exchange in the gas-phase are still not completely understood and more studies are needed to support the validity of such direct correlations [47,48]. Differences in the deuterated gas used, sampling time after ESI of the protein ions and the time allowed for deuterium exchange complicate the interpretation of the available data.…”
Section: Preserving Native or Near-native Protein Conformations Inmentioning
confidence: 99%
“…Differences in the deuterated gas used, sampling time after ESI of the protein ions and the time allowed for deuterium exchange complicate the interpretation of the available data. Nevertheless, recently developed instrumental setups have delivered results that suggest that solution-phase structural features can be preserved in the gas-phase [48,49,50,51]. Gas-phase fragmentation methods that are specific to surface-exposed regions, such as electron capture dissociation (ECD) and electron transfer dissociation (ETD) have also been extensively used to decipher gas-phase conformations [52,53,54,55,56,57,58,59].…”
Section: Preserving Native or Near-native Protein Conformations Inmentioning
confidence: 99%
“…The separation of many types of isomeric biomolecules has been demonstrated using DMS, including structural isomers, 23−39 stereoisomers, 20 isotopomers, 40 and protein conformers. 41 Besides separation by DMS, our instrument's configuration also enables the use of gas-phase hydrogen−deuterium exchange (HDX) experiments. 41−45 The HDX reactions occur post-DMS such that we can separate the ions first and investigate their gas-phase structures with HDX thereafter.…”
mentioning
confidence: 99%